2005
DOI: 10.1002/joc.1164
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging use of seasonal climate forecasts by farmers

Abstract: What encourages use of seasonal climate forecasts? Considerable effort is being applied in developing seasonal climate forecasts and demonstrating the potential benefits available to farmers from using seasonal climate forecasts. This study examines three factors underlying the use of seasonal climate forecasts by farmers: the level of forecast understanding by farmers, the format presentation of the forecasts, and the attitude of farmers towards the usefulness of forecasts as indicators of future rainfall. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
1
26
1
Order By: Relevance
“…probability of exceedance, median rainfall) compared with the non-user respondents. This finding may differ from McCrea et al (2005), who found the level of forecast understanding important in predicting the use of seasonal climate forecasts by grain growers in southern Queensland and northern New South Wales. Our study indicates that some seasonal forecasts maybe misinterpreted by graziers, and management decisions may have been made that were not intended.…”
Section: Use Of Seasonal Forecasts and Understanding The Terminologycontrasting
confidence: 93%
See 4 more Smart Citations
“…probability of exceedance, median rainfall) compared with the non-user respondents. This finding may differ from McCrea et al (2005), who found the level of forecast understanding important in predicting the use of seasonal climate forecasts by grain growers in southern Queensland and northern New South Wales. Our study indicates that some seasonal forecasts maybe misinterpreted by graziers, and management decisions may have been made that were not intended.…”
Section: Use Of Seasonal Forecasts and Understanding The Terminologycontrasting
confidence: 93%
“…Mail-out surveys using non-purposive sampling of farmers returned variable response rates between 6 and 52% [Childs et al 1991 (43%); Bayley et al 1994 (6%); Hayman and Alston 1999 (20%); Austen et al 2002 (52%); Keogh et al 2004aKeogh et al (43%), 2004b; Keogh et al 2005 (47%)]. Purposive sampling of selected Queensland graziers returned a 65% response rate (Paull and Hall 1999) and of selected farmers with previous experience in dryland and opportunity cropping practices in southern Queensland and northern New South Wales returned a 30% response rate (McCrea et al 2005).…”
Section: Response Ratesmentioning
confidence: 99%
See 3 more Smart Citations